Pengaruh Budaya Kerja dan Lingkungan Kerja terhadap Kinerja pada PT. Talco Creative Indonesia Kota Tangerang - Dinda Fitrah Wiliantari; Rani Kurniasari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
PT. Talco Creative Indonesia Tangerang City is a company engaged in digital marketing and social media management which runs various kinds of event programs, media releases and social media management. This company has been established since 2020 and is located in Griya Jakarta block i1 No. 24 South Tangerang, Banten Province, Indonesia. PT. Talco Creative Indonesia Tangerang City also makes a product that focuses on media relations and event organizers. As well as focusing on solving problems by providing main needs such as pre-production to post-production needs and educational needs in the form of event planning, leadership and organizational structure. The data collection methods in this thesis research are questionnaires, observations, literature studies with a population of 33 employees and using a sample of 33. Determined using saturated sampling techniques and using the SPSS version 26 program. The results of this research show that work culture has a partial and significant effect. on employee performance. The work environment has a partial and significant effect on employee performance. Work Culture and Work Environment simultaneously influence employee performance.